Counter Discourse; Cultural reading in the Iraqi - Ihsan Muhammed Jawad ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This study seeks to reveal the hypothesis (absence/presence) of a fictional discourse An Arab with an ideological characteristic, in which the characteristic of responding in writing to the the tide of the colonist and it is evident to The colonialist, and the study sets its determinants, which are based on an interrogation of a group of bloggers The Arab novelist who dealt with her subjection to the domination of the other with mechanisms and techniques inspired by it. The other (colonial) is the same, as is the case in (sarcasm and ridicule, and the use of historical storytelling and the bilateral relationship between text and margin and others.